Zinc Tablet Administration to Primer Dismenore Pain Level - Mundarti Mundarti; J. Pratikto Pratikto; Murdiyanto Triwibowo (Jurnal LINK, 2014)
The purpose of this research is to explore the influence of zinc tablet to primer dismenore pain level. It is a quantitative research with quasi experiment method, and the research plan that was used is one group pretest and posttest. Sample taking technique in this research was saturated sampling. Zinc administration was done for four days before menstruation, using 30 mg/day dose. This research statistics showed using wilcoxon statistic test, p=s is 0.001. The conclusion is there is a significant influence of zinc tablet administration to primer dismenore pain level.